Lung cancer in patients with pulmonary fibrosis: characteristics features and prognosis - Kara, Sibel; Mogulkoc, Nesrin; Kirkil, Gamze; Cetinkaya, Erdogan; Ozbudak, Omer; Kilic, Talat; Demirci Ucsular, Fatma; Demirkol, Baris; Duman, Dildar; Karadeniz, Gulistan; Koksal, Nurhan; Soyler, Yasemin; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Lung cancer is one of the significant comorbidities seen in patients with Idiopathic Pulmonary Fibrosis (IPF). However, there is limited data on non-IPF Pulmonary Fibrosis (PF) patients with lung cancer (LC). The present study aims to compare the characteristics and survival outcomes of patients diagnosed with LC in IPF and non-IPF PF. Methods: The multicenter data records of IPF and non-IPF PF patients diagnosed with lung cancer between 2010- 2022 were analyzed in this descriptive, cross-sectional, and retrospective study. Results: Of the 251 patients involved in this study [164 IPF-LC, 87 non-IPF PF-LC], 89.6% were male, the mean age was 69±7.9 years and the smoking rate was 85.7%. Honeycomb pattern was more frequently observed in IPF-LC patients [62.8%,37.9%p<0.001], whereas ground-glass opacity [33.5%,59.8%p<0.001] and emphysema [37.8%,59.8%p<0.001] were more frequently seen in non-IPF PF-LC patients. The most commonly seen histological type was squamous cell carcinoma [42.7%,33.9%], followed by adenocarcinoma [28.2%; 32.2%]. [46.4%;47.2%] and their 5-year mortality rates were high [64.6%, 63.2%]. The median survival for both groups was 2±0.22 years [median 95% CI (1.55-2.44)]. The shortest survival time was observed in non-IPF PF-LC subgroup with unclassified PF [1±0.253 years median 95% CI (0.50-1.49) (p=0.030)]. Conclusions: The majority of IPF and non-IPF PF LC patients were male, elderly, and had a high smoking rate. Squamous cell carcinoma was the most frequently seen histological type and they had short survival periods and high mortality rates. The survival period of unclassified non-IPF PF-LC patients was found to be the shortest.